Elevated Heme Oxygenase-1 Correlates With Increased Brain Iron Deposition Measured by Quantitative Susceptibility Mapping and Decreased Hemoglobin in Patients With Parkinson’s Disease - Xu, Jinghui; Xiao, Chi; Song, Weizheng; Cui, Xiangqin; Pan, Mengqiu; Wang, Qun; Feng, Yanqiu; Xu, Yunqi (Frontiers in Aging Neuroscience, 2021)
Background: Brain iron deposition, low hemoglobin (HGB), and increased heme oxygenase-1 (HO-1) have been implicated in Parkinson’s disease (PD). However, the association among them in PD is poorly studied. Objective: To explore the association of the level of HO-1 with brain iron deposition and low level of HGB in PD. Methods: A total of 32 patients with PD and 26 controls were recruited for this study. C57BL/6 male mice were used in generating 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced chronic PD model. The Levels of serum HO-1 and HGB of human subjects and mice were assayed by ELISA, blood routine test, respectively. Quantitative susceptibility mapping (QSM) was used to quantitatively analyze brain iron deposition in human subjects and mice. HO-1 inhibitor (Sn-protoporphyrin, SnPP) was used to suppress the function and expression of HO-1 in PD mice. Correlations between the concentration of serum HO-1 and iron deposition of the region of interests (ROIs), levels of HGB, between the three factors mentioned above, and scores of clinical scales were explored in PD patients. Results: This study revealed significant elevation of the serum HO-1 concentration, iron deposition within bilateral substantial nigra (SN), red nucleus (RN), and putamen (PUT) and decrease of HGB level in PD patients. There was a significantly positive correlation between the serum HO-1 concentration and iron deposition within SN, an inverse correlation between the serum HO-1 concentration and HGB level in PD patients. A significant increase in HO-1 expression of serum and iron deposition in SN was also observed in the PD mouse model, and the SnPP could significantly reduce iron deposition in the SN. Conclusions: The high level of HO-1 may be the common mechanism of iron deposition and low HGB in PD. Therefore, the findings presented in this study indicate that HO-1 correlates with brain iron deposition and anemia in PD.